THE MODERN CULTURAL LIFE OF UZBEKISTAN:CONCERTS, EXHIBITIONS, FASHION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Uzbekistan’s modern cultural landscape has experienced rapid transformation in recent decades. While traditional forms of art remain central to national identity, contemporary cultural platforms—including concerts, exhibitions, and fashion events—have expanded significantly. Major urban centers such as Tashkent now serve as hubs for musical performances, visual art showcases, and creative industry development. The interaction between heritage and global cultural trends has produced a vibrant environment that supports artistic innovation, youth creativity, and international collaboration. This paper examines the evolution of musical events, the diversification of visual art exhibitions, and the rise of the fashion industry as key components of Uzbekistan’s contemporary cultural development.